INOVASI PEMBELAJARAN PKN UNTUK MEMBENTUK KARAKTER SISWA DI ERA DIGITAL - i w. heru sanjaya; Dewa Bagus Sanjaya; I Nengah Suastika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The digital era has brought significant impacts on the development of students’ character, both positively and negatively. In this context, Civic Education (PKn) plays a strategic role in shaping students' character based on the values of Pancasila. This article aims to explore various innovative approaches in Civic Education that are relevant and effective in developing students’ character amidst rapid technological advancement. Through literature review and analysis of teaching practices in schools, it is found that digital-based approaches—such as the use of interactive media, online learning platforms, and integration of character-based content—can enhance student engagement while instilling values of nationalism, responsibility, and tolerance. Innovative Civic Education that is adaptive and contextual has proven to bridge the needs of students in the digital age with the goals of character education. Therefore, active teacher involvement is essential in designing learning experiences that are not only informative but also transformative in shaping intelligent, responsible, and morally grounded citizens.